Examining Students’ Perceptions About an Adaptive-Responsive Online Homework System and its Influence on Motivation and Learning - Salame, Issa I.; Soliman, Aisha (International Journal of Educational Technology and Learning, 2020)
Advances in technological education have made online homework an integral part of science courses in general which is especially true for general chemistry courses. Online homework, if used correctly, has the potential to improve students’ experience, and learning and performance in general chemistry courses. The purpose of this research investigation is to study students’ levels of perceptions about an adaptive-responsive online homework in terms of (1) examining students’ motivation, learning, and understanding of concepts, (2) determining the aspects of adaptive-responsive online homework that are useful to students’ learning, and (3) understanding the features in online homework that causes improvement in students’ motivation. The investigation took place at an urban, commuter, minority serving, and public college. The study subjects were recruited from student enrolled in general chemistry courses consisting of 207 research participants (N = 207). Our data suggest that students display positive levels of perceptions about the adaptive-responsive online homework and its use. Students also hold perceptions that show positive attitudes towards the online homework system and that it positively affected their motivation. Also, students list several useful aspects of the online homework system such as explanations of concepts, knowledge checks, review questions for tests, and tutorials. The adaptive-responsive online homework, according to the participants in our study, helped motivate students by helping them learn the concepts, continuously assessing their learning, checking their knowledge, and updating the topics accordingly.